Analyzing the changes in communication - de Moragas, Miquel (2016)
The evolution of communications during the last 25 years is analyzed here, taking as a point of comparison the transmission of the Olympic Games of Barcelona 1992. In the digital age the center of gravity of the power in the communication began to move from broadcasting to production and, now in a new cycle, this power begins to move from the production of contents to the control of the users / receivers own data. The research should study both the ruptures and the continuities, but to this analysis must add another fundamental challenge: analyzing the ways of adjusting or adapting these technologies to the human condition and its social context.